The Effectiveness of Silica and Activated Carbon Sand Filters in Reducing BOD, COD, and TSS Levels of Liquid Waste at Boalemo Regency Farmers and Fishermen Hospital - Putri Prisilya Bau; Herlina Jusuf; Moh. Rivai Nakoe (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Hospital liquid waste is waste from medical activities in the form of liquids containing organic compounds, toxic chemicals, and pathogenic microorganisms that are harmful to health and the environment. The BOD, COD, and TSS parameters can be used to measure the content of organic and inorganic matter in hospital liquid waste. This study aims to determine the effectiveness of silica sand and activated carbon filters in reducing the levels of BOD, COD, and TSS of liquid waste at the Boalemo Regency Farmers and Fishermen Hospital. The type of research is Quasi Experiment with a Pre Test-Post Test Group design. The sampling technique is Grab Sample. Wastewater samples were taken from a single reservoir (inlet) and analyzed before and after silica sand and activated carbon filtration. The data analysis technique uses the Paired Sample T Test. The results showed that the BOD and COD levels of hospital liquid waste before and after filtration using silica sand and activated carbon with three filters were obtained as a result of a reduction in BOD levels of 94 mg/L (75.32%) and COD of 95 mg/L (78.21%). Meanwhile, TSS levels increased by 312.1 mg/L caused by saturation of filtration media. This media has been shown to be effective in reducing BOD levels with p-value = 0.000 and COD with p-value = 0.000. However, there was no difference in TSS levels before and after the filtration of silica sand and activated carbon with p-value = 0.109. The Boalemo Regency Farmers and Fishermen Hospital is advised to monitor liquid waste and to further researchers to modify silica sand and activated carbon filtration media with other media to increase its effectiveness.